Cross-reactive antibodies to lipopolysaccharide - Gibb, Alan Patrick (The University of Edinburgh, 1993)
Lipopolysaccharide (LPS), also known as endotoxin, is a constituent of the outer membrane of Gram -negative bacteria which is toxic for humans and other animals. LPS probably plays a key part in the pathogenesis of Gram -negative bacteraemia and sepsis syndrome in humans. Cross- reactive antibodies to LPS may play a part in natural host defences, and may also be useful in the treatment of Gram - negative bacteraemia and sepsis syndrome. The structure of LPS, its toxicity, its role in Gram -negative bacteraemia and sepsis syndrome in humans, and the potential value of cross -reactive antibodies to LPS are reviewed.

The antibody response in recipients of typhoid vaccine was studied, with particular reference to the possibility that typhoid vaccine might induce the production of antibodies to the core region of LPS (LPS- core). In most recipients however the response observed was directed against specific antigens.

Urine samples from patients with suspected UTI were tested for IgG antibodies to LPS -core. Such antibodies were found to be associated with the presence of bacteriuria, although the association was not strong enough for antibody assay to be useful as a diagnostic test. Total urinary IgG was equally strongly associated with bacteriuria. This suggested that the antibodies were probably present because of non -specific leakage of serum components into the urine as a result of inflammation.

A large number of murine monoclonal antibodies (MAbs) to LPS -core had been produced by a collaborative group in Edinburgh and Basel, in the hope of producing a cross -reactive MAb which would be useful vii therapeutically. The binding of some of these MAbs to a collection of blood- culture isolates of Gram -negative bacteria was studied. The principal method used was immunoblotting with LPS prepared by proteinase K digestion. These studies showed that, in general, the MAbs bound to E. coli but not to other Enterobacteriaceae commonly isolated from blood- cultures.

There was a suggestion from initial studies with MAbs that some were specific for particular core types of E. coli. This was investigated by reacting 79 blood- culture isolates of E. coli, together with control strains, with 61 MAbs in an enzyme -linked immuvosorbent assay (ELISA). This allowed the identification of MAbs specific for E. coli core types R1, R2, and R3. The specificity of these MAbs for LPS -core was confirmed by imnunoblotting. The MAbs were used to determine the core -type of E. coli strains from blood, urine, and faeces. The association of core type with 0 type, K type, serum resistance, and susceptibility to rough -specific phage was studied. R1 was the commonest core type among E. coli from all sites, and was associated with the common 0 types.

Some cross -reactive MAbs had been produced which, unexpectedly, did not react with LPS -core. Three of these MAbs were investigated. One appeared to react with enterobacterial common antigen. The other two reacted with a low- molecular weight protein, probably the Braun lipoprotein.

Small quantities of HA -1A (Centoxin), a human MAb which is said to react with lipid A, became available towards the end of the project. The MAb bound to a variety of materials, including some Gram -positive bacteria, and could not be shown to react with LPS.